Coherences and Contingencies in the Reformed and Evangelical Theology: Dialectical Relation between Identity and Flexibility - Chandra Gunawan (Cipanas Theological Seminary, 2020)
Hermeneutics has an important role in the theological studies and has led many denominations, including the Reformed and evangelical churches, to re-evaluate how they should develop their theology in the postmodern context. This essay analyzes two characteristics of the early church namely her coherence and contingency and shows that the Reformed and Evangelicals should maintain these basic elements that she could be relevant to her contemporary without losing her identity. Contextual analysis and background analysis will help understand how the early church and fathers develop their theologies in their contexts. This study finds that hermeneutics is fundamental for theological schools in developing their subjects and for church ministries in educating her congregation; therefore, the Reformed and evangelicals should consider this discipline so that she enables properly re-contextualizing the historic tradition in this pluralistic context.